Swot Analysis Strategy for Improving the Quality of Education: a Case Study in SDN 008 Tembilahan Hulu, Indragiri Hilir District - Fadhlina, Syarifah; Afrianto, Afrianto; Kartikowati, Sri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
The phenomenon of unsatifying education has caused pessimism within society, even some believe that ecucation can no longer guarantee a better future for children so the education institutions must be aware of their strengths, weaknesses, opportunities and threats within the institutions which are expected to generate brilliant strategies for the development of the education quality. This research aims to analyze the strategies to improve the quality of education at SDN 008 Tembilahan Hulu, Indragiri Hilir Regency. This research is designed as a qualitative research using survey method in which the data collected are literature study, observation, documents, and interview. The population of this reseach are the entire school community members, but because of the reseach limitation, purposive sampling is chosen so the subject of the reseach are the principal, teachers and staffs, as well as the students’ parents education.. The researh findings are strategies to improve the quality of education as follows: 1) Empowering teachers to use information technology in the teaching and learning process. 2) Enhancing collaboration with external instructors or trainers to support extracurricular activities. 3) Intensifying supervision and monitoring activities by the school principal. 4) Making the Teacher Working Group (KKG) more effective in solving problems encountered by teachers in the teaching and learning process. 5) Developing educational facilities and infrastructure. 6) Transforming the school environment into a learning community through the 7K program (Cleanliness, Orderliness, Beauty, Comfort, Safety, Security, and a Sense of Belonging). 7) Empowering teachers through training programs to improve their performance. 8) Developing ICT-based school facilities for learning. 9) Establishing achievement clubs to develop students' potential. 10) Forming a School Program Evaluation Team. These strategies are expected to maintain, even to improve the educational quality and services at SDN 008 Tembilahan Hulu, Kabupaten Indraguru Hilir.